Reproductive Health Knowledge Correlated with Adolescent Attitudes Towards the Perception of Early Marriage - Maratus Sholichah Fitriah Hajar Kusnianto; Handayani; Intin Ananingsih; Siti Khoirul Fadila (Journal of Ners and Midwifery, 2025)
Adolescence is a transition period from childhood to adulthood to find identity. At this time there is a feeling of wanting to try new things. Early marriage is a marriage of a couple aged 19 years or can be categorized as adolescences. One of the serious problems faced by developing countries including Indonesia. The impacts of early marriage include low birth weight, spontaneous abortion, anemia and can cause defects in babies. This happens because the reproductive organs are not physiologically mature. This study aimed to determine the correlation between reproductive health knowledge and adolescent attitudes towards the perception of early marriage. This was correlation quantitative research with Cross-sectional approach. The population of this assessment was female adolescents at SMKN 1 Kademangan class XI. The sample was taken using the simple random sampling technique and obtained 48 respondents. The data analysis used Spearman rank. The research instrument used a questionnaire. From the study, it was found that there was a correlation between reproductive health knowledge and adolescent attitudes towards the perception of early marriage. Knowledge is one of the factors that can determine adolescents' attitudes towards perceptions of early marriage. Reproductive health education needs to be given to adolescents, especially female adolescents, to form attitudes and change perceptions of early marriage.